Extracorporeal methods of reducing high blood ammonia levels. Issue 2 (June 1962) - Ritchie, H. D.; Davies, D. M.; Godfrey, J. M.; Fan, P.; Johns, R. G. S.; Perrin, J.
Abstract : Laboratory studies have been made to evaluate two methods for removing ammonia from blood:— 1 The twin-coil artificial kidney was found to produce significant reductions in the ammonia content of outdated human banked blood. After one passage through the coil, levels of up to 9 μg. of ammonia nitrogen per millilitre were reduced to normal, and this effect was maintained when up to 5 litres were passed. 2 Ion-exchange resins, in particular a British resin ZK.225 having a 20% divinyl-benzene linkage, were also found to be effective. When passed from an artery directly through an autoclaved resin column to a vein, significant amounts of ammonia were removed from the blood of a dog with pronounced hyperammonaemia. No serious systemic, biochemical, or haematological effects were observed when the blood of three normal dogs was passed through resin columns. All survived, and to date no reason has been found why such a technique could not be used in clinical practice.